Sulfur‐to‐Iron Ratio as a Proxy for Degree of Organic Sulfurization - K. L. French; J. E. Birdwell (Geochemistry, Geophysics, Geosystems, 2025)
Abstract The degree of organic sulfurization is broadly relevant yet underreported. We present a statistically significant correlation between whole rock S/Fe and the measured degree of organic sulfurization in the thermally immature Cenomanian–Turonian Eagle Ford Group. This relationship shows a sink switch for sulfur from pyrite to organic matter. Excess iron and excess sulfur relative to pyrite, which are mathematically related to S/Fe, provide better insights into organic sulfurization than previous approaches that calculate excess iron relative to detrital iron based on aluminum concentrations. Organic sulfurization and S/Fe are tightly coupled in the Eagle Ford partially due to limited sulfur‐ and iron‐bearing components. Similar relationships could exist in other thermally immature, organic‐rich, anoxia‐prone, calcareous mudstones. The degree of organic sulfurization was estimated from S/Fe, which was used to map stratigraphic and regional variations of organic sulfurization across the Eagle Ford and to investigate how organic sulfurization relates to organic enrichment, organic preservation, and depositional redox chemistry. The extent of organic sulfurization is more tightly linked to organic preservation than enrichment. Together, organic sulfurization and Mo provide concordant evidence for depositional euxinia. The relationship between Mo and degree of organic sulfurization could indicate that sulfurized organic matter provides a pathway for Mo enrichment, but future work needs to disentangle direct mechanisms from indirect covariations between Mo, organic content, and degree of organic sulfurization. Whole rock elemental chemistry and programmed pyrolysis provide insights into organic sulfurization variations that can be upscaled and can guide subsequent detailed organic sulfur analyses.